Pengaruh Kecerdasan Numerik dan Motivasi Belajar terhadap Prestasi Belajar Matematika Siswa SMK Swasta Jakarta Timur - Mohamad Lutfi Nugraha (SAP (Susunan Artikel Pendidikan), 2018)
This study is intended to know whether there is a direct effect of numerical intelligence on student’s learning achievement, a direct effect of learning motivation on student’s mathematics learning achievement, a direct effect of numerical intelligence on learning motivation, and an indirect effect of numerical intelligence on student’ learning achievement through learning motivation. The research uses a survey method, with 100 randomly taken samples of people stratified by the comparison of the number of students in each Private Vocational School (SMK) in East Jakarta. The data analysis consists of descriptive analysis, Pearson correlation coefficient, determination correlation and path coefficient. The statistical test used is F test with the help of SPSS 20. The result of the research show: there is a direct effect of numerical intelligence on mathematics learning achievement , as shown by path coefficient value of -0,372; there is a direct effect of numerical intelligence on learning motivation, as seen by path coefficient value of 0,975; here is a direct effect of learning motivation on mathematics learning achievement with path coefficient value of 0,520; there is an indirect effect of numerical intelligence on mathematics learning achievement through learning motivation, as proved by path coefficient value of 0,507.